The effect of body mass index (BMI) and gestational weight gain on adverse obstetrical outcomes in pregnancies following assisted reproductive technology as compared to spontaneously conceived pregnancies. Issue 2 (March 2019) - Frankenthal, Dvora; Hirsh-Yechezkel, Galit; Boyko, Valentina; Orvieto, Raoul; Ron-El, Raphael; Lerner-Geva, Liat; Farhi, Adel
Abstract: Objective: To compare the effect of pre-pregnancy body mass index (BMI) and inappropriate gestational weight gain (GWG) on adverse obstetrical outcomes among women undergoing assisted reproductive technology (ART) treatments as compared to spontaneously-conceived (SC) pregnancies. Methods: This prospective cohort study included 1058 pregnant women from two medical centres; 504 women who conceived following ART treatments and 554 who conceived spontaneously. The women were recruited at 8 weeks of gestation and follow-up telephone interviews were conducted 6 weeks after delivery. Obstetrical outcomes included pregnancy hypertension, gestational diabetes (GD), low birth weight (LBW) (<2500 g) and small for gestational age (SGA). Multivariate analyses were used to assess the effect of pre-pregnancy BMI and inappropriate GWG on these obstetrical outcomes adjusted for risk factors. Results: The effect of pre-pregnancy BMI and inappropriate GWG on adverse obstetrical outcomes did not differ between ART and SC pregnancies. Pre-pregnancy obesity was found to be associated with increased risk for pregnancy hypertension (OR = 2.16; 95%CI 1.16–4.03), GD (OR = 2.89; 95%CI 1.61–5.17), caesarian section (OR = 1.77; 95%CI 1.10–2.85) and SGA (OR = 1.91; 95%CI 1.05–3.46). GWG below recommendations was associated with increased risk for GD (OR = 1.73; 95%CI 1.06–2.82) and SGA (OR = 1.69; 95%CI 1.17–2.40) while GWG above recommendations was associated with increased risk for pregnancy hypertension (OR = 1.77; 95%CI 1.02–3.06). Conclusions: Pre-pregnancy obesity and inappropriate GWG were associated with adverse obstetrical outcomes in both ART and SC pregnancies. Emphasis should be given on the importance of an optimal pre-pregnancy BMI and appropriate GWG during pregnancy.